Effects of time-of-day on the noradrenaline, adrenaline, cortisol and blood lipidome response to an ice bath - Alexander Braunsperger; Maximilian Bauer; Chaima Ben Brahim; Lea Seep; Dominik Tischer; Mirko Peitzsch; Jan Hasenauer; Sieglinde Hechenbichler Figueroa; Anna Worthmann; Joerg Heeren; Kenneth A. Dyar; Karsten Koehler; et al. (Scientific Reports)
Abstract While the effect of time-of-day (morning versus evening) on hormones, lipids and lipolysis has been studied in relation to meals and exercise, there are no studies that have investigated the effects of time-of-day on ice bath induced hormone and lipidome responses. In this crossover-designed study, a group of six women and six men, 26 ± 5 years old, 176 ± 7 cm tall, weighing 75 ± 10 kg, and a BMI of 23 ± 2 kg/m2 had an ice bath (8–12 °C for 5 min) both in the morning and evening on separate days. Absence from intense physical exercise, nutrient intake and meal order was standardized in the 24 h prior the ice baths to account for confounders such as diet or exercise. We collected venous blood samples before and after (5 min and 30 min) the ice baths to measure hormones (noradrenaline, adrenaline, and cortisol) and lipid levels in plasma via liquid chromatography mass spectrometry shotgun lipidomics. We found that ice baths in the morning increase plasma fatty acids more than in the evening. Overall plasma lipid composition significantly differed in-between the morning and evening, and only in the morning ice bathing is accompanied by significantly increased plasma fatty acids from 5.1 ± 2.2% to 6.0 ± 2.4% (P = 0.029) 5 min after and to 6.3 ± 3.1% ( P = 0.008) 30 min after. Noradrenaline was not affected by time-of-day and increased significantly immediately after the ice baths in the morning by 127 ± 2% (pre: 395 ± 158 pg/ml, post 5 min: 896 ± 562 pg/ml, P = 0.025) and in the evening by 144 ± 2% (pre: 385 ± 146 pg/ml, post 5 min: 937 ± 547 pg/ml, P = 0.015). Cortisol was generally higher in the morning than in the evening (pre: 179 ± 108 pg/ml versus 91 ± 59 pg/ml, P = 0.013; post 5 min: 222 ± 96 pg/ml versus 101 ± 52 pg/ml, P = 0.001; post 30 min: 190 ± 96 pg/ml versus 98 ± 54 pg/ml, P = 0.009). There was no difference in the hormonal and lipidome response to an ice bath between women and men. The main finding of the study was that noradrenaline, adrenaline, cortisol and plasma lipidome responses are similar after an ice bath in the morning and evening. However, ice baths in the morning increase plasma fatty acids more than in the evening.